Spatial assessment of drought hazard, vulnerability and risk in Bangladesh - Shahid, S. (Nova Science Publishers, Inc., 2013)
A conceptual framework, which emphasizes the combined role of hazard and vulnerability in defining risk, is used for the spatial assessment of drought risk in Bangladesh. The spatial extent of droughts of different severities in multiple time scales are mapped by using standardized precipitation index method within a geographical information system. The key social and physical factors that define drought vulnerability in the context of Bangladesh are identified and corresponding thematic maps in district level are prepared. Composite drought vulnerability map is developed through the integration of those thematic maps. The risk is computed as the product of the hazard and vulnerability. The study reveals that the areas with extremely high drought risk are concentrated in the northwest Bangladesh. Analysis of seasonal rainfall distribution and rainfall reliability reveals that high variation of annual rainfall has made the northwest Bangladesh more prone to droughts. On the other hand, higher poverty rates, dependency on agriculture and irrigation have made the region more vulnerable to droughts. In the context of global warming, most of the climatic models project more frequent and extreme floods and droughts in South Asia. Due to the land use changes, Bangladesh has already shown an increased frequency of droughts in recent years. A study is also carried out to envisage future droughts scenario in Bangladesh in the context of climate change. Analysis of long-term rainfall trend shows that rainfall in Bangladesh has increase significantly at a rate of 5.25mm/year in last fifty years. However, it is found that the drought in Bangladesh has no relation with rainfall amount; rather, it depends on inter-annual variability of rainfall. Significant relation between annual rainfall in Bangladesh and ENSO index indicates a teleconnection between droughts in Bangladesh and ENSO index. As it is still not clear about the effect of climate change on ENSO, it is not possible to come to a decision about climate change impacts on drought in Bangladesh.